2009
DOI: 10.1007/s00299-009-0812-1
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of GhAGP4 gene expression repressed the initiation and elongation of cotton fiber

Abstract: Cotton fibers, important natural raw materials for the textile industry, are trichomes elongated from epidermal cells of cotton ovules. To date, a number of genes have been shown to be critical for fiber development. In this study, the roles of genes encoding fasciclin-like arabinoglactan proteins (FLAs) in cotton fiber were examined by transforming RNA interfering (RNAi) construct. The RNAi according to the sequence of GhAGP4 caused a significant reduction of its mRNA level, and the expression of other three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 42 publications
0
39
0
1
Order By: Relevance
“…Cotton DNA and RNA were extracted and transferred to membranes as described previously (Zhu et al, 2005;Li et al, 2010). A fragment of NPTII was used as a probe for Southern blotting for transgene verification.…”
Section: Southern and Northern Blottingmentioning
confidence: 99%
“…Cotton DNA and RNA were extracted and transferred to membranes as described previously (Zhu et al, 2005;Li et al, 2010). A fragment of NPTII was used as a probe for Southern blotting for transgene verification.…”
Section: Southern and Northern Blottingmentioning
confidence: 99%
“…They were sterilized and then placed in liquid BT medium supplemented with 50 mM H 2 O 2 or 2 mM of the NADPH oxidase inhibitor DPI (Sigma; Li et al, 2010). The samples were collected for RNA extraction after 48 h of culture.…”
Section: Cotton Ovule Culture and Treatment With H 2 O 2 Or Nadph Oximentioning
confidence: 99%
“…The methods of genomic DNA isolation and Southern blotting were according to Li et al (2010). The probe for PDF1 gene detection was the small fragment digested from the cDNA sequence inserted in pSPORT with HindIII (Tu et al, 2007).…”
Section: Southern and Northern Blotting And Qrt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, GhMYB25 and GhMYB25-like regulate early fiber development (Machado et al, 2009;Walford et al, 2011). A study reported that GhAGP4 plays a role in fiber initiation and elongation of cotton, but its molecular mechanism in regulating fiber development still remains unclear (Li et al, 2010b). In our previous study, several fiber-preferential genes encoding FLAs were identified in cotton (Huang et al, 2008).…”
mentioning
confidence: 99%